Membaca Arena Baru Subpolitik Anak Muda dalam Memaknai Risiko Industri Ekstraktif - Erwinton Simatupang; Vandy Yoga Swara (Jurnal Studi Pemuda, 2019)
This article reveals the dynamics of youth subpolitics engagement amidst concern about environmental, social and economic risks of extractive industry operations. By focusing specifically on one of industrial locations as a case study, we explore how young people reflect nowadays and future various risks. This research uses a qualitative method with descriptive approach. Data is collected through focus group discussion (FGD), interview, and documentation. Behind youth subpolitics engagement discourse, we found that a change designed by young people leads to the risks. At this point, youth subpolitics engagement attempts to capitalize the risks that they initially against. At micro level, it turns out that a dominant actor controls youth subpolitics engagement. Applying the theoretical approach of strategic action fields developed by Neil Fligstein and Doug Mc Adam, we analyze how the dominant actor changes an arena of youth subpolitics engagement in dealing with the risks of extractive industry. As a result, young people depend on extractive industry operations.